Safety and immunogenicity of an anti-Middle East respiratory syndrome coronavirus DNA vaccine: a phase 1, open-label, single-arm, dose-escalation trial. Issue 9 (September 2019) - Modjarrad, Kayvon; Roberts, Christine C; Mills, Kristin T; Castellano, Amy R; Paolino, Kristopher; Muthumani, Kar; Reuschel, Emma L; Robb, Merlin L; Racine, Trina; Oh, Myoung-don; Lamarre, Claude; Zaidi, Faraz I; et al.
Summary: Background: Middle East respiratory syndrome (MERS) coronavirus causes a highly fatal lower-respiratory tract infection. There are as yet no licensed MERS vaccines or therapeutics. This study (WRAIR-2274) assessed the safety, tolerability, and immunogenicity of the GLS-5300 MERS coronavirus DNA vaccine in healthy adults. Methods: This study was a phase 1, open-label, single-arm, dose-escalation study of GLS-5300 done at the Walter Reed Army Institute for Research Clinical Trials Center (Silver Spring, MD, USA). We enrolled healthy adults aged 18–50 years; exclusion criteria included previous infection or treatment of MERS. Eligible participants were enrolled sequentially using a dose-escalation protocol to receive 0·67 mg, 2 mg, or 6 mg GLS-5300 administered by trained clinical site staff via a single intramuscular 1 mL injection at each vaccination at baseline, week 4, and week 12 followed immediately by co-localised intramuscular electroporation. Enrolment into the higher dose groups occurred after a safety monitoring committee reviewed the data following vaccination of the first five participants at the previous lower dose in each group. The primary outcome of the study was safety, assessed in all participants who received at least one study treatment and for whom post-dose study data were available, during the vaccination period with follow-up through to 48 weeks after dose 3. Safety was measured by the incidence of adverse events; administration site reactions and pain; and changes in safety laboratory parameters. The secondary outcome was immunogenicity. This trial is registered at ClinicalTrials.gov (number NCT02670187 ) and is completed. Findings: Between Feb 17 and July 22, 2016, we enrolled 75 individuals and allocated 25 each to 0·67 mg, 2 mg, or 6 mg GLS-5300. No vaccine-associated serious adverse events were reported. The most common adverse events were injection-site reactions, reported in 70 participants (93%) of 75. Overall, 73 participants (97%) of 75 reported at least one solicited adverse event; the most common systemic symptoms were headache (five [20%] with 0·67 mg, 11 [44%] with 2 mg, and seven [28%] with 6 mg), and malaise or fatigue (five [20%] with 0·67 mg, seven [28%] with 2 mg, and two [8%] with 6 mg). The most common local solicited symptoms were administration site pain (23 [92%] with all three doses) and tenderness (21 [84%] with all three doses). Most solicited symptoms were reported as mild (19 [76%] with 0·67 mg, 20 [80%] with 2 mg, and 17 [68%] with 6 mg) and were self-limiting. Unsolicited symptoms were reported for 56 participants (75%) of 75 and were deemed treatment-related for 26 (35%). The most common unsolicited adverse events were infections, occurring in 27 participants (36%); six (8%) were deemed possibly related to study treatment. There were no laboratory abnormalities of grade 3 or higher that were related to study treatment; laboratory abnormalities were uncommon, except for 15 increases in creatine phosphokinase in 14 participants (three participants in the 0·67 mg group, three in the 2 mg group, and seven in the 6 mg group). Of these 15 increases, five (33%) were deemed possibly related to study treatment (one in the 2 mg group and four in the 6 mg group). Seroconversion measured by S1-ELISA occurred in 59 (86%) of 69 participants and 61 (94%) of 65 participants after two and three vaccinations, respectively. Neutralising antibodies were detected in 34 (50%) of 68 participants. T-cell responses were detected in 47 (71%) of 66 participants after two vaccinations and in 44 (76%) of 58 participants after three vaccinations. There were no differences in immune responses between dose groups after 6 weeks. At week 60, vaccine-induced humoral and cellular responses were detected in 51 (77%) of 66 participants and 42 (64%) of 66, respectively. Interpretation: The GLS-5300 MERS coronavirus vaccine was well tolerated with no vaccine-associated serious adverse events. Immune responses were dose-independent, detected in more than 85% of participants after two vaccinations, and durable through 1 year of follow-up. The data support further development of the GLS-5300 vaccine, including additional studies to test the efficacy of GLS-5300 in a region endemic for MERS coronavirus. Funding: US Department of the Army and GeneOne Life Science.